Recurrent variant of unknown significance in KCNH2 classified through functional characterisation. (19th May 2022) - Copier, JS; Bootsma, M; Wilde, AAM; Bertels, RA; Bikker, H; Christiaans, I; Koopmann, TT; Lommerse, AAJ; Bezzina, CR; Verkerk, AO; Barge-Schaapveld, DQCM; Lodder, EM
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Dutch Research Council (NWO Talent Scheme) Background: Variants in KCNH2, the gene encoding the hERG channel and responsible for the cardiac rapid delayed rectifier K+ current (IKr), have been linked to Long QT Syndrome type 2 (LQTS2). The KCNH2-p.S906L variant has been found in eight, small unrelated families with variable clinical pictures and incomplete penetrance of LQTS2. Purpose: Due to the small size of the families, co-segregation analysis is limited. Functional studies were performed to evaluate the effect of the variant on channel functionality. Thereby assessing if KCNH2-p.S906L leads to functional changes explanatory for the phenotype. Methods: Clinical data of the patients and family members were collected thereby, creating an overview of the phenotype. The biophysiological properties of the hERG channel were assessed by manual whole-cell patch-clamp, using HEK293a cells expressing (i) the wild type (WT) KCNH2, (ii) KCNH2-p.S906L alone (homozygous, hm) or KCNH2-p.S906L in combination with WT (heterozygous, Hz). Results: Assessment of the clinical data of the patients and family members shows an incomplete and low penetrance of the LQTS2. All carriers were heterozygous for the variant. In carriers of the KCNH2-p.S906L variant, LQTS2 severity was very variable, ranging from asymptomatic, to life-threatening arrhythmic events. The KCNH2-p.S906L variant reduced current density in a dosage-dependent manner compared to KCNH2-WT. The current density was reduced by 63, and 54% in KCNH2-p.S906L-Hm and KCNH2-p.S906L-Hz, respectively. Changes in gating properties were absent, except for activation kinetics in KCNH2-p.S906L-Hm. In these cells, an increase in the time constant, and a positive shift in voltage dependency of activation were observed. Conclusions: Both the reduced current density and changes in activation kinetics suggest the variant to result in a moderate loss-of-function of the hERG channel, fitting with the observed LQTS2. These observed functional changes in hERG combined with the reduced penetrance in the affected individuals suggest that this variant in KCNH2 is a risk factor for LQTS2.